A new sliding mode control strategy to improve active power management in a laboratory scale microgrid - Oscar Gonzales-Zurita; Jean-Michel Clairand; Guillermo Escrivá-Escrivá (International Journal of Electrical Power & Energy Systems)
In recent years, the widespread use of single-phase voltage source inverters (SPVSIs) has led to significant challenges in managing microgrids’ electrical energy, particularly regarding efficiency and robustness. Most SPVSIs on the market use proportional–integral (PI) control for their closed-loop regulation process. Although the PI controller represents an effective method for power management in a microgrid, it exhibits challenges in achieving proper system response and stability for active power generation. This study proposes a robust control solution based on the second-order sliding mode control (SMC-2) algorithm to overcome the mentioned challenges. This algorithm employed a non-conventional sliding surface to improve the microgrid’s capacities for energy management. The research was conducted in a PSCAD environment, where a real industrial SPVSI with PI control was emulated and then optimized using the SMC-2. The employed tuning method was the particle swarm optimization (PSO) technique. This method ensures global optimum optimization of the SMC-2 control parameters. Different operating scenarios were performed to demonstrate the superiority of SMC-2 over PI. The SMC-2 achieved in less time than PI, active power references over a range of 0 to 1000 W, and obtained lower performance indices based on reference tracking error. The microgrid under study is located at Universitat Politècnica de València.